Surveillance one year post focal cryotherapy for clinically significant prostate cancer using mpMRI and PIRADS v2.1: An initial experience from a prospective phase II mandatory biopsy study - Jyothirmayi Velaga; Kae Jack Tay; Guanqi Hang; Yu Guang Tan; John SP Yuen; Melvin Chua; Rajan T. Gupta; Thomas J. Polascik; Nye Thane Ngo; Yan Mee Law (European Journal of Radiology Open, 2023)
Objectives: Multiparametric magnetic resonance imaging (mpMRI) surveillance post focal cryotherapy (FT) of prostate cancer is challenging as post treatment artefacts alter mpMRI findings. In this initial experience, we assessed diagnostic performance of mpMRI in detecting clinically significant prostate cancer (csPCa) after FT. Materials and methods: This single-centre phase II prospective clinical trial recruited 28 men with localized csPCa for FT between October 2019 and April 2021. 12-months post FT mpMRI were performed prior to biopsy and sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of all mpMRI positive subjects were analysed. Chi square goodness of fit test correlated biopsy positive PIRADS3 (P3) and PIRADS4/5 lesions with histology grade group. One way ANOVA test assessed performance of ADC values in differentiating csPCa, non csPCa and benign lesions. Results: Sensitivity, specificity, PPV and NPV of mpMRI were 100%, 14.28%, 53.84% and 100% for subjects with histologically proven cancer. Correlation of PIRADS v2.1 scores with histologically proven prostate cancer was statistically significant (p < 0.5). Correlation of P3 lesions with non-csPCa was statistically significant (p < 0.02535). Higher ADC value was associated with benign histology (adjusted odds ratio OR 0.97, 95% confidence interval: 0.94, 0.99) (p = 0.008). Among the malignant lesions, higher ADC value was associated with non-csPCa (adjusted OR: 0.97; 95% CI: 0.95, 0.99) (p = 0.032). Conclusion: mpMRI is highly sensitive in detecting residual cancer. ADC values and PIRADS scores may be of value in differentiating csPCa from non-csPCa with a potential for risk stratification of men requiring re-biopsy versus non-invasive surveillance of remnant prostate.